The development of teacher interns' competencies of science instructional design and implementation using STEM activity based on DIY, Tinker and maker frameworks - Suthida Chamrat; Pongsathorn Suyamoon (Journal of Technology and Science Education, 2024)
The objective of this research was to examine the impact of STEM activity based on Diy, Tinker and Maker frameworks on developing teacher interns' competency in science instructional design and implementations. These activities involve the integration of science, technology, engineering, and mathematics principles, fostering self-regulated learning, creativity, and innovation among students. The research encompassed the design of five STEM activity modules, including a UVC Box Experiment, Digital pH Meter, Air Sensor, Startup & Rare Earth Board Game, and Motion Sensor activity, which were shared with teacher interns via Google Classroom using tutorial videos, slides, and additional materials to enhance their skills. An examination of 26 lesson plans from 13 teacher interns was carried out through content analysis, within a learning model guided by High Impact Practices (HIPs) spanning six domains: well-structured lessons, project-based learning, reflection, learning progression framework, student-centered approach, and Technological Pedagogical Content Knowledge (TPACK). The results showed that the application of the DIY, Tinker, and Maker framework through STEM activities effectively improves teacher interns' competencies in science instructional design and implementation. Particularly noteworthy was the gradual enhancement observed from the initial to the subsequent implementation across all HIPs domains, especially in showcasing TPACK. Nonetheless, the research also identified variations in competency levels, prompting contemplation among students. The importance of developing activities that stimulate student reflection emerged as a key point to consider. This indicates that STEM activities based on the concepts of DIY, Tinker, and Maker should emphasize such reflective practices. The insights obtained from this study could advance the enhancement of teacher interns' skills and encourage further exploration of the topics discussed.